An Urgent Appeal to the Government of Canada to Proclaim our Northern Identity - England, John H. (ARCTIC, 2000)
. Looming new developments of unprecedented scale now present for Northerners both significant opportunities and challenges, especially if long-term cultural vitality and a sustainable environment are to be maintained. Northern Canada is also a key archive and bellwether for global climate change, and understandably it has become increasingly the focus of foreign researchers, whose resources vastly exceed those of Canadians. In light of this northern transformation, this article revisits Canada's ongoing unpreparedness in northern science and technology ., contrasts Canada's inactivity with proactive steps being taken by other countries with well-structured polar agendas, and recommends recently proposed solutions as a long-awaited remedy. .